Pola Komunikasi Pernikahan Adat Jawa di Desa Batankrajan, Kecamatan Gedeg, Kabupaten Mojokerto - Chofifha, Aditya Melantika; Pardianto, Pardianto (Dimar Jaya Publishing, 2023)
This research aims to analyze the communication patterns of traditional Javanese wedding processions in Batankrajan Village, Gedeg District, Mojokerto Regency. The main focus of this research is to understand how traditional Javanese wedding communication patterns are used to preserve and maintain Javanese cultural values. This study uses qualitative research methods with a cultural approach. The results of the research reveal that communication patterns in traditional Javanese wedding processions in Batankrajan village are very organized and influenced by strong cultural norms. Communication is carried out through various means, including formal verbal communication such as speeches and statements, as well as non-verbal communication demonstrated through traditional rituals and symbols. During the event, linear communication is clearly visible in the form of announcements and ritual implementation, while primary communication patterns emerge in the interactions between the bride and groom's family and invited guests